Peran Aparat Pengawasan Internal Pemerintah Terhadap Akuntabilitas Pengelolaan Keuangan Negara Dalam Penanganan Pandemi Covid-19 - Erika Ayu Oktaviani; Waluyo Waluyo; Sapto Hermawan (Jurnal Discretie, 2022)
This legal research has aims to see how teh role of teh government’s internal control apparatus is to account for the management of state finances in handling the Covid-19 pandemic. This legal research is a prescriptive type of normative legal research using a statute approach and conceptual approach. The types of legal materials used are in the form of primary and secondary legal materials. The technique of collecting legal materials used is literature study techniques, while the technique of analyzing legal materials used is the deductive method. The results of this legal research indicate that the impact of the Covid-19 pandemic on the economic sector has triggered a spike in the poverty rate. The government provides a number of aids to increase people’s purchasing power. The allocation of funds for handling Covid-19 is a sector prone to corruption. Therefore, a supervision is needed by the government’s internal supervisory apparatus in preventing corrupt practices by irresponsible parties through coordination betwen policy makers and the role of the executor to prevent fraus committed by irresponsible parties.